IRAK4 Deficiency in a Patient with Recurrent Pneumococcal Infections: Case Report and Review of the Literature - Gobin, Karina; Hintermeyer, Mary; Boisson, Bertrand; Chrabieh, Maya; Ghandil, Pegah; Puel, Anne; Picard, Capucine; Casanova, Jean-Laurent; Routes, John; Verbsky, James (Frontiers in Pediatrics, 2017)
Primary immune deficiencies are genetic defects of the innate or adaptive immune system resulting in a propensity to infections. The innate immune system is the first line of defense against pathogens, and is critical to recognize microbes and start the inflammatory cascade. Sensing of microbes occurs by a number of pathogen recognition receptors, resulting in the activation of inflammatory signal transduction pathways, such as the activation of NF-B. Herein we describe a case of IRAK4 deficiency, a key signal transduction molecule of toll-like and IL-1 receptors. We highlight the complexities in diagnosis of these disorders, and review genetic defects of the NFB pathway.